Visualization of educational information with the use services of cloud technology - N. V. Zhytyenyova (Academy of Cognitive and Natural Sciences, 2014)
The purpose of the paper is the theoretical justification for the use of information visualization with the use services of cloud technology in educational process secondary school. Object of research supports the educational process in secondary school. The object is to use visualization training information with the use services of cloud technology. The feasibility of the use of these technologies in education due to their compliance psychological peculiarities inherent in the present generation of students and the need for a compact representation of the training material in the manner most convenient to its perception, understanding, learning and remembering. It is shown that the use of visualization develops cognitive interest of students, makes it possible to create a positive emotional atmosphere in the classroom and facilitates implementation of intersubject connections in learning. However, visualization is a powerful didactic tool, the use of which has to be motivated, pedagogically appropriate methodically backed up. In our opinion, the problem of training of future teachers to effective use of technology of visualization in teaching activities is a perspective direction for further research.